Perylene Monoimide as a Versatile Fluoroprobe: The Past, Present, and Future - Roy, Rupam; Khan, Aasif; Chatterjee, Oendrila; Bhunia, Sukomal; Koner, Apurba Lal (Organic Materials, 2021)
Perylene dyes have transcended their role as simple colorants and have been reinvigorated as functional dyes. Based on the substitution at the peri-position by six-membered carboxylic imides, the perylene family is principally embellished with perylene diimides (PDIs) and perylene monoimides (PMIs). Perylene dyes are widely acclaimed and adorned on account of their phenomenal thermal, chemical, and photostability juxtaposed with their high absorption coefficient and near-unity fluorescence quantum yield. Although symmetric PDIs have always been in the limelight, their asymmetrical counterpart PMI is already rubbing shoulders, thanks to the consistent efforts of several scientific minds. Recently, there has been an upsurge in engendering PMI-based versatile organic architectures decked with intriguing photophysical properties and pertinent applications. In this review, the synthesis and photophysical features of various PMI-based derivatives along with their relevant applications in the arena of organic photovoltaics, photocatalysis, self-assembly, fluorescence sensing, and bio-imaging are accrued and expounded, hoping to enlighten the less delved but engrossing realm of PMIs.Table of content:1 Introduction2 Advantages of PMI over PDI3 Challenges in Working with PMI and Ways to Overcome4 Various Aspects of Reactivity of Different Positions5 Synthesis of the PMI core6 Synthesis of PMI Derivatives6.1 Bromination of PMI6.2 Synthesis of PMI Derivatives using Coupling Reactions6.2.1 Suzuki Coupling6.2.2 Sonogashira Coupling6.2.3 Buchwald–Hartwig Coupling Reaction6.3 Nucleophilic Substitution Reactions6.4 Peri-Annulation Reaction7 Photophysical Properties of PMI8 Singlet Fission Properties9 Förster Resonance Energy Transfer with PMI10 Symmetry Breaking Charge Transfer Properties11 Panchromatic Light Absorption Properties of PMI12 Acid/Base Sensitivity of PMI13 NIR-Absorbing PMI14 Achieving of Triplet State Using PMI15 Solid-State Emissive PMI16 Thermo-Responsive Materials with PMI17 Photo-Responsive PMI Derivatives18 Electrochemical Properties of Rylene Derivative19 Self-Assembling Properties of PMI Derivatives20 Applications of PMI in Solar Cells21 PMIs in Bulk Heterojunction Solar Cells22 PMIs in Dye-Sensitized Solar Cells23 PMI as a Fluorescent Reporter23.1 Application of PMI Derivatives for Bio-Imaging23.2 Hydrophilic PMIs for Bio-Imaging23.3 Aggregated PMI as NIR-Emissive Fluoroprobe for Bio-Imaging24 Photocatalytic Hydrogen Generation using PMI25 PMI-Based Organocatalysis26 PMI Derivatives for Single-molecule Spectroscopy27 Host–Guest Chemistry with PMI28 Conclusions and Outlook
Keywords: rylene dyes; perylene monoimide; self-assembly; fluorescent probe; functional organic materials